2007
DOI: 10.1007/s00415-006-0444-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased serotonin transporter availability in the brainstem of migraineurs

Abstract: For decades, serotonin has been speculated to play a major role in migraine pathophysiology. The central serotonergic system is located in the raphe nuclei and the adjacent reticular formation in the brainstem. Recently, radioligands targeting the brain serotonin transport protein (SERT) have been developed. We used the highly specific SERT-radioligand (123)I-ADAM [2-((2-((dimethylamino) methyl)phenyl)thio)-5-iodophenylamine] to test the hypothesis of the mesopontine serotonergic system being involved in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 45 publications
1
48
0
2
Order By: Relevance
“…Likewise, these findings are in agreement with the increase in the serotonin availability observed in the brainstem of migraineurs as a response to altered endogenous 5-HT levels. 35 Despite the increase in [ 11 C]DASB binding in the ipsilateral midbrain, a lack of changes in both SERT and 5-HT 2A availability has been observed in the contralateral hemisphere after ischemia. These results stand in contrast to the increased D 2 dopaminergic receptor availability observed in the contralateral hemisphere after 2-hour MCAO, which could have a key role in the functional recovery after cerebral ischemia.…”
Section: Serotoninergic Changes After Cerebral Ischemiamentioning
confidence: 99%
“…Likewise, these findings are in agreement with the increase in the serotonin availability observed in the brainstem of migraineurs as a response to altered endogenous 5-HT levels. 35 Despite the increase in [ 11 C]DASB binding in the ipsilateral midbrain, a lack of changes in both SERT and 5-HT 2A availability has been observed in the contralateral hemisphere after ischemia. These results stand in contrast to the increased D 2 dopaminergic receptor availability observed in the contralateral hemisphere after 2-hour MCAO, which could have a key role in the functional recovery after cerebral ischemia.…”
Section: Serotoninergic Changes After Cerebral Ischemiamentioning
confidence: 99%
“…SERT modulates serotonin neurotransmission by removing serotonin from the synaptic cleft back to the presynaptic neuron. An imaging study that used a more SERTselective radioligand [ 123 I]ADAM also demonstrated significantly increased brainstem SERT availability in migraineurs than in healthy subjects [13]. Increased brainstem SERT availability together with low serotonin synthesis rate [14] and increased serotonin turnover [15,16] during headache-free phase reflect low synaptic serotonin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In-house PET template was made from 12 healthy subjects. Posterior part of the midbrain was chosen because approximately 80 % of the serotonergic neurons reside within the raphe nuclei [13]. ROIs did not include the anterior part of the midbrain which is abundant in DATs.…”
Section: Brain [ 18 F]fp-cit Petmentioning
confidence: 99%
“…These observations are in line with previous neuroimaging and molecular biology studies. By using neuroimaging methods (SPECT-images coregistered with MRI-scans) (Schuh-Hofer et al, 2007) it was shown that there is an increased availability of 5-HTT in brainstem in migraine patients during the interictal period. The recent PET-study also confirms that the 5-HTT availability is crucial in the pathomechanisms of migraine (Park et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a neuroimaging study increased 5-HTT availability in the mesopontine brainstem of migraineurs has been detected (Schuh-Hofer et al, 2007). Data show that the vast majority of 5-HTT is localized on the axolemma, in the vicinity of the synapses, and along the axons as well.…”
Section: Introductionmentioning
confidence: 96%